Synthesis, Antibacterial Activity and Cytotoxicity of Novel Janus Peptide Dendrimers - Pan, Junzhu; Guo, Li; Ouyang, Liang; Yin, Dongqin; Zhao, Yi (Synlett, 2012)
In an attempt to find new antibacterial agents, a series of well-defined Janus peptide dendrimers, which feature multiple anionic groups and amphiphilic structure, were synthesized and characterized in detail. The antibacterial activities of all the synthesized dendrimers were tested and screened by using the two-fold serial dilution method. Several compounds showed activity against E. coli, S. aureus, methicillin-resistant S. aureus, and E. faecalis. Further cytotoxicity assays showed that the antibacterial dendrimers were nontoxic against HEK293.
Keywords: Janus dendrimer; peptide dendrimer; amphiphilic; antibiotics; antibacterial activity